3D Printing Technology: A Proposed Framework for Implementation - Alkhulaifi, Nasser (2019)
3D printing (3DP) technology is a manufacturing method that allows the user, whether organisations or individuals, to produce solid three-dimensional objects that are “printed” from raw materials based on access to 3D computer data. This manufacturing process could lead to a whole new era in production methods and revolutionise manufacturing by improving product affordability, speed, customisation and precision. Furthermore, many experts believe that 3DP technology will influence different aspects of today’s supply chains, especially the inventories, warehouses, production processes and lead times. However, adopting such technology can be challenging for companies as it is strongly believed that such implementation is a strategic decision for companies that requires significant planning, analysis and integration between different parties. Implementation frameworks are therefore needed to provide general guidance and to classify the key factors and considerations that would support companies to deliver a successful implementation. This research combines a questionnaire research approach with background theory to analyse the different implementation frameworks of advanced manufacturing systems and develops an implementation framework for 3DP technology. The proposed framework divides the adoption considerations and factors into four key dimensions: strategic considerations, technical considerations, organisational and supply chain considerations, and external considerations. The significant contribution of the study is the proposed 3DP implementation framework which companies in different fields can utilise to develop their implementation strategies and plans.